Analisis Kemampuan Literasi Sains Siswa Kelas V SD Negeri 02 Indralaya Selatan - Lestari, Nadia Putri; Akhbar, M. Taheri; Selegi, Susanti Faipri (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The aim of this research is to describe the scientific literacy abilities of grade 5 students at SD Negeri 02 South Indraya. This research method is descriptive qualitative data analysis techniques and this research is data reduction, presenting data and drawing conclusions. The research results show that the scientific literacy abilities of grade 5 students at SD Negeri 02 Indra Selatan is in the good category based on the results of observation interviews and student questionnaires and the results are 21 students in the good category, 4 students in the very good category and 3 students in the fair category with an average score of 72.8%, so teachers need to improve students' chassis literacy through good learning. leads to real or contextual life and applies a caring attitude towards the environment.